Konsep Manusia Ideal dalam Persepektif Suhrawardi Al-Maqtul - Ernita Dewi (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2015)
Ideal man in the perspective of Suhrawardi called a perfect man (insan kamil). They are the leaders who represent the position as caliph in the earth. Man is a perfect creature which has many advantages compared with other creatures, because they have senses and intellect that are able to penetrate the boundaries of the senses toward non-material objects indirectly through the process of syllogism. In addition, the five senses and the intellect of man is also endowed the hearts by Allah, such that the human heart can directly capture the non-material objects known as intuition. The ability to unite between rational knowledge and intuition with the guidance of the Qur'an and the Hadith, will form the perfect man to implement all the goodness in the life of this universe. This article reviews the ideal man according to al-Suhrawardi Maqtul stating that the perfect man is very important in creating a harmonious world order